The Alchemist Book Review as a Medium for Strengthening High School Students' Critical Thinking - Ramadan, Trisno Mas'ud; Sabrina, Sabrina; Amelia, Reilla; Luthfiya, Qonita; Kumaladewi, Nia (Universitas Negeri Semarang, 2025)
The era of globalization necessitates that the younger generation acquire essential 21st-century skills, with critical thinking being one of the most pivotal. However, empirical evidence reveals that adolescents still exhibit relatively low proficiency in this area, despite its vital contribution to academic success, extracurricular achievement, and everyday decision-making. Addressing this concern, a community service initiative introduced an innovative educational strategy through a book discussion program aimed at fostering critical thinking. The chosen text, The Alchemist, offers profound narratives on life journeys and personal introspection. Implemented at SMAN 10 Depok, the program engaged 11th-grade students using the Focus Group Discussion (FGD) method, encompassing intensive reading, collaborative dialogue, and reflective presentations. The intervention resulted in notable enhancement of students’ analytical, interpretive, and evaluative skills, alongside the cultivation of critical and reflective discourse. Furthermore, the activity contributed to the revitalization of literacy culture among learners. Consequently, the book discussion initiative demonstrated its effectiveness as a contemporary pedagogical approach to strengthening adolescents’ critical thinking competencies.